OPTIMIZATION OF LOCAL TREATMENT METHODS FOR ORAL PAIN SYNDROMES IN POSTMENOPAUSAL WOMEN - Masharipov Sirojbek Madiyorovich; Kuryazov Akbar Kuranbayevich; Khabibova Nazira Nasulloyevna (Modern American Journals, 2025)
The study examines the optimization of local treatment methods for oral pain syndromes in postmenopausal women, focusing on Burning Mouth Syndrome (BMS) as a prevalent neuropathic condition. The research analyzes key pathogenic mechanisms, including estrogen deficiency-induced alterations in salivary composition, small-fiber neuropathy, and dysfunction of trigeminal nociceptive pathways. The role of psychological comorbidities, such as anxiety and depression, in modulating pain perception is considered.A targeted approach to local therapy is proposed, incorporating topical anesthetics, neuroprotective agents, and saliva substitutes. The impact of correcting mucosal irritation caused by dental factors is evaluated. The findings support the necessity of a multidisciplinary treatment model integrating dental, neurological, and endocrinological interventions to improve therapeutic efficacy and patient outcomes.
Keywords: Burning Mouth Syndrome, postmenopause, neuropathic pain, local therapy, estrogen deficiency, salivary dysfunction, trigeminal nerve, small-fiber neuropathy, oral pain management, psychological comorbidities, multidisciplinary treatment.